2015
DOI: 10.1177/1010539515595860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Type 2 Diabetes Mellitus in Vietnam

Abstract: This systematic review examined trends in the prevalence of type 2 diabetes mellitus (T2DM) and identified its risk factors among adults in Vietnam. PubMed, Web of Science, Wiley Online Library, and Scopus databases were searched to identify relevant literature. The search yielded 10 studies, including 2 national surveys and 8 regional investigations. National prevalence estimates of T2DM were 2.7% in 2002 and 5.4% in 2012. The estimates for the northern region were 1.4% in 1994 and 3.7% in 2012 and those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 67 publications
6
66
2
2
Order By: Relevance
“…8 Male sex has often been identified as a risk factor for development of DM in the cat 4,9,10 and DM in cats also shares several predisposing factors with Type 2 DM in people, including increasing age, physical inactivity and obesity. [9][10][11] In cats, obesity is proposed to cause insulin resistance through various mechanisms, including altered secretion of adipokine hormones and changes in lipid metabolism. 12,13 Not all obese or older cats develop DM, however, so other genetic or environmental factors might determine whether an individual eventually becomes diabetic.…”
mentioning
confidence: 99%
“…8 Male sex has often been identified as a risk factor for development of DM in the cat 4,9,10 and DM in cats also shares several predisposing factors with Type 2 DM in people, including increasing age, physical inactivity and obesity. [9][10][11] In cats, obesity is proposed to cause insulin resistance through various mechanisms, including altered secretion of adipokine hormones and changes in lipid metabolism. 12,13 Not all obese or older cats develop DM, however, so other genetic or environmental factors might determine whether an individual eventually becomes diabetic.…”
mentioning
confidence: 99%
“…This information is in disagreement with another study that observed a higher risk of DM2 in men due to a higher responsibility of women regarding their selfcare (21) . However, it was supported by systematic review about prevalence and incidence of risk factors for DM2 in Vietnam, in which the gender factor did not show considerable difference and pointed out the lack of consistency in the association between gender and diabetes requires further investigation (22) . Nevertheless, national and international studies respectively, revealed that men have higher risk of developing DM2 (2,23) .…”
Section: Discussionmentioning
confidence: 97%
“…Studies [33][34][35][36] analyzed the factors of risk in a population of adults and observed that the risk for developing T2DM mainly relates to gender, age, family history of T2DM, physical inactivity, hypertension, high BMI, modified triglycerides, obesity/ overweight and urban residence, factors also found in the Arab population described in an integrative review [14]. This review identified and discussed most of those factors; however, two must have a better emphasis.…”
Section: Discussionmentioning
confidence: 99%